Case report: The MSI-L/p-MMR metastatic rectal cancer patient who failed systemic therapy responds to anti-PD-1 immunotherapy after stereotactic body radiation-therapy - Liu, Shijin; Zhang, Yiran; Lin, Yujian; Wang, Peize; Pan, Yunlong (Frontiers in Immunology, 2022)
Background: Traditionally, patients with microsatellite stability (MSS)/ proficient mismatch repair (p-MMR) metastatic colorectal cancer (mCRC) have had low benefit from immunotherapy. Although more and more studies are exploring how to break this bottleneck, including conventional treatments such as chemotherapy, targeted therapy, and stereotactic body radiation-therapy (SBRT) combined with immunotherapy. But, as we all know, the results are not satisfactory. Case Presentation: We report a special case of a rectal cancer patient with programmed death-ligand 1 (PD-L1) negative, MSS/p-MMR, tumor mutational burden-low (TMB-L) and liver metastases only, who responded well to immunotherapy after systemic therapy failure. The presence of liver metastases only as well as multiple progression of metastases were the main features of this patient. The patient survived more than 40 months after diagnosis. Conclusions: This case indicates that the patients with liver metastases from MSS/p-MMR type rectal cancer can also respond to anti-PD-1 immunotherapy. The reason for this may be that SBRT modifies the immune-status of the body. Thus, the SBRT (targeting liver metastases) may improve the benefit from immunotherapy in patients with MSS/p-MMR colorectal cancer with liver metastases.